2004
DOI: 10.1051/0004-6361:20047085
|View full text |Cite
|
Sign up to set email alerts
|

Emission of CO, C I, and C II in W3 Main

Abstract: Abstract. We used the KOSMA 3m telescope to map the core 7 × 5 of the Galactic massive star forming region W3 Main in the two fine structure lines of atomic carbon and four mid-J transitions of CO and et al. 1991), this data set allows us to study the physical structure of the molecular cloud interface regions where the occurence of carbon is believed to change from C + to C 0 , and to CO. The molecular gas in W3 Main is warmed by the far ultraviolet (FUV) field created by more than a dozen OB stars. Detailed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

48
201
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 158 publications
(253 citation statements)
references
References 78 publications
48
201
4
Order By: Relevance
“…These (sub)millimeter continuum condensations detected from the ground are ∼ 3 orders of magnitude denser than typical CO clumps (e.g. Kramer et al 1998) and feature large ( 50%) mean column density contrasts over their parent background clouds, strongly suggesting they are self-gravitating. The latter is directly confirmed by line observations in a number of cases.…”
Section: Prestellar Core Mass Functions From Ground-based Observationsmentioning
confidence: 81%
See 3 more Smart Citations
“…These (sub)millimeter continuum condensations detected from the ground are ∼ 3 orders of magnitude denser than typical CO clumps (e.g. Kramer et al 1998) and feature large ( 50%) mean column density contrasts over their parent background clouds, strongly suggesting they are self-gravitating. The latter is directly confirmed by line observations in a number of cases.…”
Section: Prestellar Core Mass Functions From Ground-based Observationsmentioning
confidence: 81%
“…Core mass functions (histograms with error bars) derived from our Herschel observations of the Polaris (left) and Aquila (right) regions, which reveal of total of 302 starless cores and 541 candidate prestellar cores, respectively Könyves et al 2010). The IMF of single stars (corrected for binaries -e.g., Kroupa 2001), the IMF of multiple systems (e.g., Chabrier 2005), and the typical mass spectrum of CO clumps (e.g., Kramer et al 1998) are shown for comparison. Log-normal fits to the observed CMFs are superimposed.…”
Section: First Results From Herschel On the Cmf-imf Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kramer et al 1998). However, the mass distribution for the fragments within the clouds has a log-normal form, indicative of a turbulent origin for these sub-structures (Hennebelle & Chabrier 2008).…”
mentioning
confidence: 98%